Topical Combination Delivery of Benzoyl Peroxide and Adapalene Niosomal Gel for Acne Treatment (Asian Journal of Pharmaceutics (AJP), 2019)
Aim and Objective: Adapalene (ADP) is very effective in 0.01% strength, but it causes skin erythema in theapplied area. ADP and benzoyl peroxide (BPO) are the most commonly used drugs in treatment of acne. ADP actsas keratolytic agent and BPO acts as potent antibacterial agent, both the drugs are used individually in a cyclicmanner. The combination of both drugs if used judiciously can be used to cure mild to moderate acne effectivelyby acting on pathogenetic site. The successful treatment of acne depends on the maintenance of effective drugconcentration levels at the affected site. The main benefit over liposome is that the lipids are replaced by non-ionicvesicles and hence the preparation is totally non-antigenic. Materials and Methods: The non-ionic surfactantslike SPANs are obtained from synthetic sources, and hence the quality is maintained same all the time. The ADPwas incorporated into niosomes using SPAN 60 and cholesterol was used as a stabilizer. Various ratios of SPAN 60,cholesterol, Stearic acid, BPO, and ADP were tried and optimized. Various process parameters were also optimizedfor the rotary flask evaporation method. The present study investigates the effect of niosomal coadministrationof BPO and ADP in term of in vitro skin retention study and in vivo antiacne effects. These vesicular carriers,because of their improved percutaneous delivery and better skin retention, have proved to be very useful inenhancing therapeutic index of drugs used for tropical diseases. The niosomal dispersion was incorporated intoCarbopol gel. The gel was kept for 3 months accelerated stability studies. Results and Discussion: The niosomaldispersion was evaluated for various parameters such as vesicle size, shape, and morphology by transmissionelectron microscopy. In vitro and in vivo studies were carried out. The drug release pattern from gel was evaluatedon the basis of in vitro studies and skin irritation studies on rabbit skin. Conclusion: The in vitro study showssustained release gel effects whereas the in vivo study shows no signs of irritation on the applied skin area.